The behaviour of Ni and its isotopes during early diagenesis of Mn oxide-rich abyssal sediments - Sarah Fleischmann; Jianghui Du; Brian Haley; James McManus; Mingzhao Sun; Derek Vance (Geochimica et Cosmochimica Acta, 2026)

Coupled Imaging and THM-Damage Modeling of Supercritical CO2 Fracturing in Coal - Liyuan Liu; Yaohui Li; Derek Elsworth; Tao Wang; Hongguang Ji; Xiaodong Sun; Tao Yang; Kaikai Zhao; Jiong Wang (Rock Mechanics and Rock Engineering, 2026)

In-situ stress measurements over the Eastern Himalayan syntaxis and implications for seismicity - Xianghui Qin; Chongyuan Zhang; Derek Elsworth; Wen Meng; Zhihao Liang; Chengjun Feng; Yuehui Yang; Dongsheng Sun (Tectonophysics, 2025)

The process analysis of converting ferronickel into high nickel matte - Qifan Zhou; Ying Liu; Honghong Sun; Biwen Yang; Sanping Liu; Derek O. Northwood; Kristian E. Waters; Yanqiu Xia; Hao Ma (Minerals Engineering, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Trace metal evolution of the Late Cretaceous Ocean - Mingzhao Sun; Corey Archer; Florian Scholz; Tim Sweere; Derek Vance (Chemical Geology, 2025)

Optimizing tomato waste hydrolysate for enhanced fucoxanthin biosynthesis in mixotrophic cultivation of Isochrysis galbana - Xi-Wen Fan; Han Sun; Derek M. Ayittey; Zhi-gang Zhou; Carol Sze Ki Lin; Tao Tang; Zheng Sun (Bioresource Technology, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Status, challenges and pathways to the sustainable use of wild species - Jean-Marc Fromentin; Marla R. Emery; John Donaldson; Ganesan Balachander; Elizabeth S. Barron; Ram P. Chaudhary; Marie-Claire Danner; Maria A. Gasalla; Agnès Hallosserie; Marwa Halmy; Christina Hicks; Daniel Kieling; et al. (Global Environmental Change, 2023)

The C-BIG Repository: an Institution-Level Open Science Platform - Samir Das; Rida Abou-Haidar; Henri Rabalais; Sonia Denise Lai Wing Sun; Zaliqa Rosli; Krishna Chatpar; Marie-Noëlle Boivin; Mahdieh Tabatabaei; Christine Rogers; Melanie Legault; Derek Lo; Clotilde Degroot; et al. (Neuroinformatics, 2022)
In January 2016, the Montreal Neurological Institute-Hospital (The Neuro) declared itself an Open Science organization. This vision extends beyond efforts by individual scientists seeking to release individual datasets, software tools, or building platforms that provide for the free dissemination of such information. It involves multiple stakeholders and an infrastructure that considers governance, ethics, computational resourcing, physical design, workflows, training, education, and intra-institutional reporting structures. The C-BIG repository was built in response as The Neuro’s institutional biospecimen and clinical data repository, and collects biospecimens as well as clinical, imaging, and genetic data from patients with neurological disease and healthy controls. It is aimed at helping scientific investigators, in both academia and industry, advance our understanding of neurological diseases and accelerate the development of treatments. As many neurological diseases are quite rare, they present several challenges to researchers due to their small patient populations. Overcoming these challenges required the aggregation of datasets from various projects and locations. The C-BIG repository achieves this goal and stands as a scalable working model for institutions to collect, track, curate, archive, and disseminate multimodal data from patients. In November 2020, a Registered Access layer was made available to the wider research community at https://cbigr-open.loris.ca , and in May 2021 fully open data will be released to complement the Registered Access data. This article outlines many of the aspects of The Neuro’s transition to Open Science by describing the data to be released, C-BIG’s full capabilities, and the design aspects that were implemented for effective data sharing.

The role of corals on the abundance of a fish ectoparasite in the Great Barrier Reef - José Ricardo Paula; Derek Sun; Vasco Pissarra; Pauline Narvaez; Rui Rosa; Alexandra S. Grutter; Paul C. Sikkel (Coral Reefs, 2021)

Differential deployment of sanctioning mechanisms by male and female host trees in a gynodioecious fig–wasp mutualism - Xiao‐Wei Zhang; Derek W. Dunn; Xiao‐Lan Wen; Bao‐Fa Sun; Rui‐Wu Wang (Ecology, 2019)
In some insect nursery pollination mutualisms, plant hosts impose net costs to uncooperative “cheater” symbionts. These “sanctions” promote mutualism stability but their precise adaptive nature remains unclear. In fig–wasp mutualisms host trees ( Ficus spp.) are only pollinated by female agaonid wasps whose larvae only use galled fig flowers as food. In actively pollinated systems, if wasps fail to pollinate, sanctions can result via fig abortion, killing all wasp offspring, or by increased offspring mortality within un‐aborted figs. These sanctions result from selective investment to pollinated inflorescences, a mechanism present in almost all angiosperms. To more fully understand how selective investment functions as sanctions requires the measurement of variation in their costs and benefits to both hosts and symbionts. Gynodioecious fig‐tree–fig‐wasp mutualisms are particularly suitable for this because pollen and wasps are produced only in the figs of “male” trees and seeds only in the figs of “female” trees. Male and female trees thus incur different net costs of pollen absence, and costs of sanctions to pollen‐free “cheater” wasps only occur in male trees. We used the actively pollinated host tree Ficus hispida and introduced into male and female figs either 1, 3, 5, 7, or 9 all pollen‐laden “cooperative” (P+) or all pollen‐free “cheater” (P−) wasps. Abortion in both male and female trees was highest in P− figs, with P− fig abortion higher in females (~90%) than in males (~40%). Fig abortion was negatively associated with foundress number mainly in P+ figs; in P− figs abortion was only weakly associated with the number of “cheater” wasps, especially in female figs. In un‐aborted male figs, wasp offspring mortality was higher in P− figs than in P+ figs, and in P− figs correlated positively with foundress (cheater) number. Increased offspring mortality was biased against female wasp offspring and likely resulted from reduced larval nutrition in unpollinated flowers. Variation in selective investment to P− figs thus reflects costs and benefits of pollen absence/presence to hosts, variation that translates directly to net costs to cheater wasps.

Pseudobacciger cheneyae n. sp. (Digenea: Gymnophalloidea) from Weber’s chromis (Chromis weberi Fowler & Bean) (Perciformes: Pomacentridae) at Lizard Island, Great Barrier Reef, Australia - Derek Sun; Rodney A. Bray; Russell Q.-Y. Yong; Scott C. Cutmore; Thomas H. Cribb (Systematic Parasitology, 2014)

Discriminative host sanctions in a fig–wasp mutualism - Rui-Wu Wang; Derek W. Dunn; Bao Fa Sun (Ecology, 2014)
In some mutualisms, cooperation in symbionts is promoted by hosts sanctioning “cheats,” who obtain benefits but fail to reciprocate. In fig–wasp mutualisms, agaonid wasps pollinate the trees ( Ficus spp.), but are also exploitative by using some flowers as larval food. Ficus can sanction cheats that fail to pollinate by aborting some un‐pollinated figs. However, in those un‐pollinated figs retained by trees, cheats successfully reproduce. When this occurs, wasp broods are reduced, suggesting sanctions increase offspring mortality within un‐pollinated figs. We investigated sanction mechanisms of abortion and larval mortality against wasp cheats in the monoecious Ficus racemosa by introducing into figs 1, 3, 5, 7, or 9 female wasps (foundresses) that were either all pollen‐laden (P+) or all pollen‐free (P−). The abortion rates of P− figs were highest (∼60%) when single foundresses were present. Abortion declined with increased foundresses and ceased with seven or more wasps present, irrespective of pollination. In un‐aborted figs, wasp fitness (mean offspring per foundress) declined as foundress number increased, especially in P− figs. Reduced broods in P− figs resulted from increased larval mortality of female offspring as foundress number increased, resulting in more male‐biased sex ratios. Overall sanctions estimated from both abortion rates and reduced offspring production strengthened as the number of cheats increased. In a second experiment, we decoupled pollination from wasp oviposition by introducing one pollen‐free foundress, followed 24 h later by seven pollen‐laden ovipositor‐excised wasps. Compared with P+ and P− single‐foundress figs, delayed pollination resulted in intermediate larval mortality and wasp fitness, which concurred with patterns of female offspring production. We conclude that fig abortion reflects both pollinator numbers and pollen presence. Sanctions within P− figs initiate soon after oviposition and discriminate against female offspring, thus reducing the benefits to cheats from adaptively biasing their offspring sex ratios. We suggest that costs to cheats via these discriminative sanctions are likely to promote stability in this mutualism.

Uranium reduction and microbial community development in response to stimulation with different electron donors - Melissa Barlett; Hee Sun Moon; Aaron A. Peacock; David B. Hedrick; Kenneth H. Williams; Philip E. Long; Derek Lovley; Peter R. Jaffe (Biodegradation, 2012)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)